Atuação profissional e vivência do cirurgião-dentista na estratégia do programa de saúde da família - Araújo, Yanne Pinheiro de (2005)
The purpose of this research was to analyze the working profile of dentists from the Family Health Program (PSF Programa de Saúde da Família, Brasil) of some Municipal Districts of Rio Grande do Norte (Brazil) in order to understand the way they handle the experience acquired with the work developed in that Program. This discussion evolves a reflection about the perspectives of consolidation of the FHP as well as the possible advancements of the Brazilian Unified Health System (SUS - Sistema Único de Saúde). The target population was composed of dentists from the FHP of Rio Grande do Norte. Thus we performed twenty-one interviews orientated by a semi-structured guidebook with open questions and identification data. We opted for recording the speech of all the professionals in order to ensure the accuracy of the information gathered. The main results found were: predominance in the female gender; the majority of dentists has no post graduation courses; in those few cases of dentists with some post-graduation a lack of correlation with Public or Collective Health was observed; the dentists interviewed present a profile directed to clinical activities; the dentists used to develop basic restorative and periodontic treatment, simple surgeries and educative and preventive activities, even though the last two ones are carried out in an extremely traditional way (lectures and topical application of fluoride). In addition, as biggest difficulties to manage the work dentists pointed out the lack of permanent and consumer material, inadequate infrastructure, no transport to take them to distant places, no integration with the Health Family Team, technical difficulty such to perform educative and preventive activities as to provide adequate service to a repressed lawsuit. The results indicate the existence of a necessity to lead them to reflect and redirect their practices. In order to reach this aim it must be considered as initial measure the investment and encouragement toward to permanent education as well as a close follow-up and evaluation of the actions developed by them